2012
DOI: 10.1096/fj.12-206060
|View full text |Cite
|
Sign up to set email alerts
|

T lymphocytes from patients with systemic lupus erythematosus are resistant to induction of autophagy

Abstract: Autophagy, the cytoprotection mechanism that takes place under metabolic impairment, has been implicated in the pathogenesis of autoimmunity. Here, we investigated the spontaneous and induced autophagic behavior of T lymphocytes from patients with systemic lupus erythematosus (SLE) compared with that of T lymphocytes from healthy donors by measuring the autophagy marker microtubule-associated protein 1 light chain 3 (LC3)-II. No significant differences in spontaneous autophagy were found between T lymphocytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
108
2
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(127 citation statements)
references
References 62 publications
(84 reference statements)
15
108
2
2
Order By: Relevance
“…[16][17][18] This deregulation could contribute to autoreactive T-cell survival and can be put in line with the deregulation of both macroautophagy and chaperone-mediated autophagy (CMA) in B cells that has been recently described to occur in lupus. 19,20 To date, however, these data remain correlative and no study has been published describing an in vivo model, prone to systemic autoimmunity, with specific autophagy deletion in B cells.…”
mentioning
confidence: 71%
“…[16][17][18] This deregulation could contribute to autoreactive T-cell survival and can be put in line with the deregulation of both macroautophagy and chaperone-mediated autophagy (CMA) in B cells that has been recently described to occur in lupus. 19,20 To date, however, these data remain correlative and no study has been published describing an in vivo model, prone to systemic autoimmunity, with specific autophagy deletion in B cells.…”
mentioning
confidence: 71%
“…C'est le cas de l'hydroxychloroquine, utilisée en routine, ou la rapamycine et le peptide P140 [45,46] qui sont en essais cliniques. De plus, l'autophagie est dérégulée dans les LT, dans des modèles murins de lupus, et chez les patients atteints de LED [28,[47][48][49]. Les LT de ces patients présentent une charge en autophagosomes plus importante que des LT de sujets sains [47].…”
Section: Autophagie Des Lymphocytes Et Physiopathologieunclassified
“…The alteration of mitophagy leads to defective clearance of mitochondria and formation of megamitochondria [55]. Another research showed that T lymphocytes from lupus patients were resistant to autophagic induction and presented up-regulation of genes which negatively regulate autophagy [57]. It suggests that autophagy-resistant T lymphocytes could be selected because of chronic exposure to specific antibodies in SLE.…”
Section: Autophagy In Rheumatic Diseases Systemic Lupus Erythematosusmentioning
confidence: 99%